Influence of the wetting properties of polymeric adhesives on the mechanical behaviour of cork agglomerates - Teixeira, M J; Fernandes, A C; Saramago, B; Rosa, M E; Bordado, J C (JOURNAL OF ADHESION SCIENCE AND TECHNOLOGY, 1996)
A series of adhesives, polyurethane prepolymers with alkane chains of different functionalities, were used in the production of cork agglomerates. The polymeric structure varied from long, linear chains in adhesive M1 (14% isocyanate groups) to short, branched chains in adhesive M4 (30% isocyanate groups). The wetting properties of the adhesives were studied through surface tension and contact angle measurements of the polymeric liquids deposited on cork substrates. The mechanical behaviour of the cork agglomerates was studied through compression and three-point bending tests, and the agglomerate structure was analysed by scanning electron microscopy (SEM). The relationship between the structural and wetting characteristics of the adhesives and the mechanical properties of the agglomerates was investigated. The experimental results indicate that it is the work of adhesion for the adhesive/cork system, and not only the contact angle, which determines the mechanical resistance of the cork agglomerate.
Keywords: adhesives; cork agglometares; mechanical properties; WETTING

THE EFFECT OF LONG-TERM TREATMENT AT 100-DEGREES-C-150-DEGREES-C ON STRUCTURE, CHEMICAL-COMPOSITION AND COMPRESSION BEHAVIOR OF CORK - Rosa, M E; Pereira, H (HOLZFORSCHUNG, 1994)
The effects of heating of cork in air at 100-degrees-C and 150-degrees-C for up to 42 days have been studied. Dimensional and mass changes induced by heat treatment were measured and the chemical composition was analysed. The thermal degradation of cork is small for short periods of treatment but increases with time and temperature. Cork looses after 42 days of treatment 6.8 % of its mass at 100-degrees-C and 19.9 % at 150-degrees-C. Cork extractives and polysaccharides were found to be the most temperature labile components. The cellular structure, observed by scanning electron microscopy, did not change with treatment in these conditions. Compression curves of untreated and heat treated cork samples were obtained, which show an increase of compression strength upon heating for short exposure periods and a decrease for longer ones. The changes observed in the compression behaviour of cork treated at 100-degrees-C and 150-degrees-C were related to the chemical composition changes induced by heat treatment.
Keywords: c; Cellular materials; Cork; mechanical properties

Growth stresses and strains in cork - FORTES, M A; Rosa, M E (Wood science and technology, 1992)
A detailed study of the growth stresses and strait~s in the cork sheI1 of the cork-oak was undertaken based on experimentally determined constitutive relations for cork in tension and compression. The stresses depend on the thicknesses of the cork shell and of the back layer around the cork shell, on the radius of the trunk and on its increase due to growth. The circumferential stresses in the cork shell and back layer are tensile and increase with increasing distance to the tree axis. The radial stresses are compressive and decrease with increasing distance to the tree axis. The strains due to growth are not recovered when the cork boards are removed, unless the boards are heated, for example, by immersion in boiling water. Other consequences of the growth stresses are analysed, such as the occurrence of corrugations in the lateral cell walls of cork, the variation of width of the successive growth rings and the occurrence of cracks in the back layer and outer cork layers.
Keywords: back layer; Cork; growth stresses (voyant)